2022
DOI: 10.3389/fgene.2022.968598
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of immune-based biomarkers and deep learning models for Alzheimer’s disease

Abstract: Background: Alzheimer’s disease (AD) is the most common form of dementia in old age and poses a severe threat to the health and life of the elderly. However, traditional diagnostic methods and the ATN diagnostic framework have limitations in clinical practice. Developing novel biomarkers and diagnostic models is necessary to complement existing diagnostic procedures.Methods: The AD expression profile dataset GSE63060 was downloaded from the NCBI GEO public database for preprocessing. AD-related differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…According to the descriptions and figures with the ANN diagrams in those articles and after checking the documentation of the R package that they used for ML, either those figures were incorrect, or those authors have erroneously used the word “layers” instead of “neurons”. He et al [ 130 ] concluded that, after screening seven hub genes from AD-related differentially expressed genes, hub genes are key in the immune microenvironment. The RF in [ 131 ] was able to screen six important genes, critical for separating AD and normal samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the descriptions and figures with the ANN diagrams in those articles and after checking the documentation of the R package that they used for ML, either those figures were incorrect, or those authors have erroneously used the word “layers” instead of “neurons”. He et al [ 130 ] concluded that, after screening seven hub genes from AD-related differentially expressed genes, hub genes are key in the immune microenvironment. The RF in [ 131 ] was able to screen six important genes, critical for separating AD and normal samples.…”
Section: Resultsmentioning
confidence: 99%
“…Three articles included in this review utilized a RF for feature selection and an ANN with only 5 hidden neurons for classification [130][131][132]. According to the descriptions and figures with the ANN diagrams in those articles and after checking the documentation of the R package that they used for ML, either those figures were incorrect, or those authors have erroneously used the word "layers" instead of "neurons".…”
Section: Cross-sectional Studies Based On Blood Biomarkers and Genesmentioning
confidence: 99%
“…Gray modules are used to place genes that are not attributed to any of the modules and are not considered to be of clinical analysis. Correlations between model eigengenes (ME) and clinical characteristics were calculated using Pearson correlation coefficients for each module, including Brown, Red, Purple and Yellow for the four modules at P<0.05 [ 31 ]. We then calculated the relationship between gene expression levels and clinical performance for these four modules using Pearson correlation coefficients.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of some research, ferroptosis has been shown to be involved in the pathological process of AD ( Ayton et al, 2020 ; Sun Y. et al, 2022 ; Wang et al, 2022c ). In the previous studies, to promote the development of diagnosis, researchers have explored candidate factors such as immune-based biomarkers ( He et al, 2022 ), DNA methylation-related biomarkers ( Chen et al, 2022 ) and aging-related biomarkers ( Zhang Q. et al, 2022 ). The diagnostic link between ferroptosis and AD is not well studied.…”
Section: Discussionmentioning
confidence: 99%